EFFECT OF DEXMEDETOMIDINE ON DOSE REQUIREMENT OF PROPOFOL AND THIOPENTONE INDUCTION IN PATIENTS UNDER GENERAL ENDOTRACHEAL ANESTHESIA - Senapati, Laxman K; Samanta, Priyadarsini (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The present study was undertaken to assess the effect of dexmedetomidine as a premedicant on dose requirement of induction agents, thiopentone and propofol in patients undergoing various surgeries under general endotracheal anesthesia under the bispectral index (BIS) guidance. Methods: A double-blinded randomized controlled study was conducted during the year 2014–2015 among 120 patients aged 18–55 years with American Society of Anesthesiologists' physical status Score I or II and Mallampati Grades I and II. After obtaining informed consent, all the eligible patients were randomly assigned to one of the four groups each containing 30 patients: Group SP (control group) - saline infusion before induction with propofol, group DP - dexmedetomidine infusion before induction with propofol, group ST (control group) - saline infusion before induction with thiopentone, and group DT - dexmedetomidine infusion before induction with thiopentone. Results: The mean dose of propofol required was 95.0±6.15 mg and 55.0±7.0 mg in group SP and DP, respectively, whereas the requirement of thiopentone was 6.6±0.93 mg/kg in group ST as opposed to 4.8±0.58 mg/kg in group DT. The decrease in the dose requirement in dexmedetomidine groups than the control groups was statistically significant and also dose reduction in dexmedetomidine was more in DP group compared to that in DT group (p<0.001). Conclusion: Dexmedetomidine as a preanesthetic medication significantly decreases intraoperative anesthetic requirement of thiopentone and propofol, and dose requirement is significantly less in case of propofol as compared to thiopentone.